Dr. Bombay & Inner Circle in da house. - Dr. Bombay; Inner Circle; WARNER Music (Malaysia). (Kuala Lumpur : Warner Music (Malaysia), 1998)
Contains two tracks from two different artists, the first taken from the album Rice & Curry, the second taken from the album Jamaika Me Crazy.
CD 1 : Calcutta (Taxi, Taxi, Taxi) / Dr. Bombay (4:06) -- Obla Di-Obla Da / Inner Circle (4:04).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Popular music; Popular music -- 1991-2000.; Reggae music